Reverse shoulder arthroplasty for deltoid-deficient shoulder following latissimus dorsi flap transfer. Case report - Dosari, Mohamed Al Ateeq Al (Int J Surg Case Rep, 2017)
INTRODUCTION: The usual indication for reverse shoulder arthroplasty is glenohumeral arthritis with inadequate rotator cuff and intact deltoid muscle. We report here a case of reverse shoulder arthroplasty using a lattisimus dorsi flap in a patient with deltoid-deficient shoulder following a gunshot injury. PRESENTATION OF THE CASE: The patient was an otherwise healthy 51-year-old male with a history of gunshot injury of the left shoulder 2006. Upon presentation in 2011, the patient had a loss of most of his shoulder bony and muscular structures. Due to deltoid muscle deficiency, the patient underwent Lattisimus Dorsi muscle flap followed by reverse shoulder arthroplasty in order to establish an upper limb function. Upon discharge, 11 days after the surgery, the patient was able to achieve 150° flexion and 90° abduction while in the supine position and 45° in each direction, while sitting. He was able to perform internal rotation (behind back) up to the level of the L1 vertebra, assisted active abduction of 90°, and external rotation of 20°. Power tests showed power of grade 4/5 for both shoulder flexion and extension and grade 2+/5 for both abduction and adduction. At the last follow up one year after the operation, The patient still had passive pain-free full range of motion, but no progress in active range of motion beyond that upon discharge. CONCLUSION: Reverse shoulder arthroplasty after Latissmus dori flap in patient with deltoid deficient shoulders can be a successful and reproducible approach to treat such conditions.